Simultaneous elimination of hydrated silica, arsenic and phosphates from real groundwater by electrocoagulation using a cascade-shaped up-flow reactor. (20th January 2020) - Castañeda, Locksley F.; Coreño, Oscar; Nava, José L.
Abstract: This paper deals with the elimination of hydrated silica, arsenic, and phosphates from real groundwater collected in central Mexico (arsenic 22 μg L −1, hydrated silica 161 mg L −1, sulfate 50 mg L −1, phosphate 0.41 mg L −1, pH 7.6 and conductivity 508 μS cm −1 ) by electrocoagulation (EC), using a cascade-shaped up-flow reactor with a six-cell stack open to the atmosphere at the top. Aluminum plates were used as electrodes. The influence of both current density (4 ≤ j ≤ 10 mA cm −2 ) and mean linear flow rates (1.2 ≤ u ≤ 4.8 cm s −1 ) in the EC reactor on the removal efficiency of hydrated silica, arsenic, and phosphates were examined. The best removal of arsenic after EC (reaching a residual concentration, C As = 1.5 μg L −1 ) was obtained at j = 10 mA cm −2 and u = 1.2 cm s −1, meeting the World Health Organization (WHO) recommendation (<10 μg L −1 ), while the residual concentrations of hydrated silica, phosphates and sulfates were C hs = 42 mg L −1, C PO 4 3 − = 0.03 mg L −1 and C SO 4 2 − = 35 mg L −1, respectively. The experimental conditions at j = 10 mA cm −2 and u = 1.2 cm s −1, produced a large amount of coagulant (85.4 mg L −1 ), so this condition was repeated in a second round of the EC process to further reduce the concentration of hydrated silica. This time, C hs = 2.6 mg L −1 and C SO 4 2 − = 30 mg L −1 were obtained with the complete abatement of arsenic and phosphates. The total cost of the EC was 1.093 USD m −3, which included the electrolytic energy consumption, the price of aluminum, the costs of pumping and confinement of sludge, emphasizing that the calculation was based on Mexican costs. SEM-EDS, XRD, XRF and FTIR analyses on flocs revealed that the coagulant reacted with silica forming aluminum silicates, while arsenic and phosphates were removed by adsorption on flocs. The partial removal of sulfates (40%) is associated with weak adsorption on aggregates. Highlights: Elimination of hydrated silica, arsenic, phosphate and sulfate from groundwater. Cascade-shaped up-flow electrocoagulation (EC) reactor with aluminum electrodes. High coagulant doses are formed at current densities of 10 mA cm −2 . Silica reacts with coagulant to form aluminosilicates and silicates as flocs. WHO guideline for As was satisfied after EC.